Psychological peculiarities of the formation and the course of maladaptive states of internship doctors in the aspect of their psychocorrection - Vyun, V. V. (Journal of Education, Health and Sport, 2016)
Tense working conditions unfavorably affect not only the somatic, but also the mental health of people working in conditions of constant neuropsychic and physical stress. The presence of signs of maladaptation (decrease in the level of professional capacity, violation of behavioral regulation, increased conflict with others, tendency to addictive and delictual behavior) leads to lack of adequate and purposeful response of such individuals, becomes individual and extreme, and contributes to erroneous actions in the process of professional activity, professional mistakes, and also contributes to further transformation into mental and behavioral disorders. Changes in higher medical education, its integration into the European educational space requires new approaches to postgraduate medical training of a doctor. Conditions for modernization of postgraduate medical education have been created. Therefore, the main tasks of postgraduate education of doctors, especially during the reform period, are to ensure both the improvement of the professional training of internship doctors and the provision of medical and psychological support to the doctors during the period of adaptation to professional activity. on the basis of a systematic approach to the study of mechanisms for the formation of maladaptive states of internship doctors to professional activity, to develop a system of their psychotherapeutic correction. three main levels of adaptation of a doctor to professional activity are identified: The high level (20.1% of men and 13.1% of women) is characterized by the high level of work capacity, psychological comfort, availability of reserves for overcoming critical situations, objective difficulties associated with disadvantages in the modern organization of the medical process. The average level (15.4% and 12.2% respectively) is characterized by a decrease in the level of efficiency and psychological comfort in crisis situations and in the presence of shortcomings in the organization of the medical process, with a rapid recovery in their solution and the preservation of psychological comfort outside the work process. The low level (8.8% of men and 6.1% of women) is characterized by the development of maladaptation, psychological discomfort in everyday life. Constant feeling of dissatisfaction with themselves and their professional activities. In 55.7% of men and 68.6% of women, maladaptation was detected. Namely, the high level of maladaptation requiring the use of urgent measures (psychological and medical) was found in 9,2% of men and 12,5% of women; the significant level of maladaptation requiring mandatory intervention by psychologists, the conduction of a rehabilitation program – in 10.3% of men, 14.0% of women; the average level of maladaptation, when it is useful to carry out the advisory work of specialists – in 36,2% and 42,1% respectively. In order to prevent and correct the disorders of adaptation to the professional activities of internship doctors, we have developed a system of medical and psychological support during the professional training period, which involves the use of integrated psychotherapeutic and psychoeducational effects; establishment of the purpose of psychotherapy as an effect on pathogenetically significant biopsychosocial factors of the development of maladaptation; differentiation of tasks and amount of psychotherapy and psychocorrection according to the type of maladaptation. It should be noted that the effectiveness of psychotherapeutic influence is possible only in conjunction with the organizational and pedagogical plan.